Research on Correlations of lncRNA ST7-AS1 with Progression and Therapeutic Targets of Esophageal Cancer - Lin, Xiao; Sun, Sijia; Zhang, JiWen; Cai, Yan; Cheng, Quan (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Esophageal cancer is a highly prevalent gastrointestinal tumor in China, resulting in a significant number of deaths annually. In this paper, we investigated the regulatory role and therapeutic potential of aberrant ST7-AS1 expression in esophageal cancer. Materials and Methods: The presence of ST7-AS1 in 125 esophageal cancer tissues was identified through RT-qPCR assays. The application of Kaplan-Meier to evaluate survival rates in patients with esophageal cancer. Cell activity was assessed by both CCK-8 and Transwell assays. The luciferase activity assay verified the association of ST7-AS1 with miR-4262. Results: ST7-AS1 expression in esophageal cancer was noticeably overexpressed compared to the control group. Patients with upregulated ST7-AS1 had shorter survival rates. Silencing ST7-AS1 reduced the proliferation level of esophageal cancer cells, as did the migration and invasion levels. Mechanistically, ST7-AS1 acted as a sponge for miR-4262, affecting the progression of esophageal cancer. This was negatively correlated with ST7-AS1. Moreover, the miR-4262 inhibitor negated the inhibitory effect of silencing ST7-AS1 on cells. Conclusion: Knockdown of ST7-AS1 may alleviate tumor progression by targeting miR-4262, indicating that ST7-AS1 is anticipated to serve as a therapeutic biomarker for patients with esophageal cancer. Cite this article as: Lin X, Sun S, Zhang J, Cai Y, Cheng Q. Research on correlations of lncRNA ST7-AS1 with progression and therapeutic targets of esophageal cancer. Turk J Gastroenterol. 2025;36(2):82-88.